Znaczenie Niemieckiej Kolei Wschodniej (die deutsche Ostbahn) w okresie międzywojennym (1918-1939) w kontekście geopolitycznym - Walkowiak, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper entitled "The significance of the German Eastern Railway during the interwar period 1918-1939 in the geopolitical context" presents the essence of the functioning of the railway in selected key contexts. The starting point is a reflection on Peter Bock's monograph "D 1 Berlin - Königsberg. Im Transit durch Danzig und durch den "polnischen Korridor". This short analysis opens up with a historical overview which takes into account the most important caesura in its history with particular emphasis on the year 1918, which due to deep changes of the geopolitical extent also brought a change in the railway's status in the strategic and strictly political sense. Another important context here is a paradigm of the so-called German East, within which the railway had functioned, and which is highlighted by referring to two significant publications: Fritz Hugo Hoffmann's "Walka o Wschod" [Fighting for the East] (1930) and Karl Thalheim's "Niemiecki Wschód jako zadanie i jako źródło siły" [The German East as an Undertaking and Source of Power] (1936).
Keywords: historia kolei żelaznej; geopolityka; traktat wersalski; II (druga) Rzeczpospolita; Rzesza Niemiecka; Polska - historia - 1918-1939; history of railroad; geopolitics; Versailles Treaty; German Reich; Second Polish Republic